1997
DOI: 10.1093/brain/120.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Corticomotor representation of the sternocleidomastoid muscle

Abstract: The topography of the cortical motor projection to the sternocleidomastoid (SCM) muscles was investigated in 15 normal subjects using the technique of transcranial magnetic stimulation. Contrary to the long-held view that the representation of the neck muscles in the motor strip is close to that of the face, our findings indicate that the projection to both the ipsilateral and contralateral SCM muscles arises from an area of cortex high up on the cerebral convexity close to the trunk representation and at a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 1 publication
9
44
1
Order By: Relevance
“…Even in the absence of TMS, contralateral neck muscle activity increased just before contralateral saccades and remained tonically elevated, and decreased just before ipsilateral saccades and remained tonically suppressed. Such phasic and tonic coupling of neck muscle activity with saccades and eccentric eye positions have been previously described in NHPs (Stuphorn et al, 1999;. However, TMS evoked a further increase in contralateral neck muscle activity only when delivered before contralateral saccades (Fig.…”
Section: Tms Over Pfc Evoked a State-dependent Neck Muscle Response Dsupporting
confidence: 78%
See 1 more Smart Citation
“…Even in the absence of TMS, contralateral neck muscle activity increased just before contralateral saccades and remained tonically elevated, and decreased just before ipsilateral saccades and remained tonically suppressed. Such phasic and tonic coupling of neck muscle activity with saccades and eccentric eye positions have been previously described in NHPs (Stuphorn et al, 1999;. However, TMS evoked a further increase in contralateral neck muscle activity only when delivered before contralateral saccades (Fig.…”
Section: Tms Over Pfc Evoked a State-dependent Neck Muscle Response Dsupporting
confidence: 78%
“…Neck muscle responses were measured while TMS coil location over the frontal cortex was varied systematically (the mapping experiment) or while the level of TMS output was varied (the intensity experiment). Our rationale for requiring the NHPs to fixate during TMS was because tonic neck muscle activity varies with eye-in-head position (Stuphorn et al, 1999;. In the mapping experiment, the intensity of TMS was set to the lowest levels capable of reliably recruiting contralateral neck muscle activity [45, 40, and 35% of maximum stimulation output (MSO) for monkeys sp, zn, and al, respectively].…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral basal ganglia involvement has also been suggested by SPECT studies showing that striatal D2 receptor binding was significantly reduced in patients with CD when compared with normal controls [41]. Bilateral rather than unilateral DBS is also supported by knowledge accumulated regarding the innervation of neck muscles [42].…”
Section: Pallidal Dbs For Cervical Dystoniamentioning
confidence: 90%
“…47 In a recent transcranial magnetic stimulation study in normal subjects, however, ipsilateral as well as contralateral sternocleidomastoid responses were evoked by stimulation of an area of cortex near the representation of the trunk. 48 Another study showed that, after amytal injection of the right internal carotid artery, all patients who were fully cooperative were able to lift and turn their heads both to the right and to the left on command. 49 Ten of the 14 patients had weakness of the right sternocleidomastoid muscle compared with the left, suggesting that most of the innervation of the sternocleidomastoid comes from the ipsilateral hemispere.…”
Section: Discussionmentioning
confidence: 99%